A Comparative Study Between Child-Centered And Teacher-Centered In Teaching English To Elementary School Students - . Musiman (Universitas Bandar Lampung, 2011)
This experimental study used two groups, randomized subjects, posttest-only design. It was conducted to know whether Child-Centered method is more effective, more efficient, and more enjoyable than Teacher-Centered method in teaching English to elementary school students. Thirty students taken randomly from the population were randomly grouped into one experimental group and one controlled group, consisting of 15 students each. The experimental group was taught using Child-Centered method, while the control group was taught using Teacher-Centered method, by the same teacher, using the same material.Observation and interview were done during the research process to collect the data about studentss feeling. Post-test was given after 10 meeting (treatments) to know the learning result. The t-test analysis to the data indicates that Child-Centered method is more effective, more efficient, and more enjoyable than Teacher-Centered method in teaching English to the fourth grade of elementary school students in SD Negeri 1 Beringin Raya, Kemiling, Bandar Lampung.